An Analysis of Verbal Humor in Preaching of Ustadz Abdul Somad - Muhammad Afdhal; Hamzah Hamzah (English Language and Literature, 2019)
There have been many studies about humor, especially verbal humor. Most of them were related to the areas of, for example situation comedy, movie, song and so on where humor can easily be found because it is the main focus of those areas. However, there were no prior studies which explore the verbal humor in the areas where its main focus is not to produce funny remarks. Therefore, the researcher attempted to find the exitence of verbal humor in such area, particularly in preaching where the main focus is to deliver religous teachings, but the existence of humor is also there. The object of this research was the preaching of Ustadz Abdul Somad. The general therory of verbal humor (GTVH) proposed by Attardo and Raskin (1991) was employed in order to analyse the humor creation process of each types of verbal humor. The results showed that Ustadz Abdul Somad produced a significant number of verbal humor, in terms of types, numbers and knowledge recources. Ustadz Abdul Somad produced 9 out 12 types of verbal humor.